2007
DOI: 10.1017/s0898588x0700020x
|View full text |Cite
|
Sign up to set email alerts
|

Policy Tragedy and the Emergence of Regulation: The Food, Drug, and Cosmetic Act of 1938

Abstract: It is now a commonplace assertion among scholars of regulation to say that new regulatory statutes follow “crises,” “tragedies,” or “scandals.” The content and form of these critical events varies considerably. They include acts of journalism or research such as the publication of the Nader Report (which purportedly led to new federal automobile safety regulations) or Upton Sinclair's The Jungle (which eased the path for the Pure Food and Drugs Act of 1906). They include instantaneous disasters such as the Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 24 publications
(3 reference statements)
0
14
0
Order By: Relevance
“…“Claimsmakers” generally seek to either expand or contain problem definitions in order to mobilize political support and resources (Cobb & Coughlin, ; Hilgartner & Bosk, ; Spector & Kitsuse, ). Policy entrepreneurs may use focusing events such as disasters, crises, failures, errors, and accidents to galvanize public attention and reframe problem definitions (Birkland, ; Birkland & Warnement, ; Carpenter & Sin, ; Kingdon, ; Lawrence & Birkland, ; Mintrom & Norman, ), though established institutions may buffer status quo definitions (Baumgartner & Jones, ; Lodge & Hood, ).…”
Section: An Alternative: the Problem Definition And Control Approachmentioning
confidence: 99%
“…“Claimsmakers” generally seek to either expand or contain problem definitions in order to mobilize political support and resources (Cobb & Coughlin, ; Hilgartner & Bosk, ; Spector & Kitsuse, ). Policy entrepreneurs may use focusing events such as disasters, crises, failures, errors, and accidents to galvanize public attention and reframe problem definitions (Birkland, ; Birkland & Warnement, ; Carpenter & Sin, ; Kingdon, ; Lawrence & Birkland, ; Mintrom & Norman, ), though established institutions may buffer status quo definitions (Baumgartner & Jones, ; Lodge & Hood, ).…”
Section: An Alternative: the Problem Definition And Control Approachmentioning
confidence: 99%
“…In the United States, triggering events have increased federal food regulation several times (e.g., U.S. Department of Agriculture, n.d.). To give but two examples, the public’s reaction to The Jungle is anecdotally credited with spawning the Federal Meat Inspection Act (Carpenter & Sin, ), and E. coli outbreaks in the 1990s led to a strengthening of centralized standards for government inspection (May, ). Notably, in one food policy issue, regulation of raw milk, scholars find that advocacy groups pressured for deregulation risk and decentralization of regulation by refocusing public attention away from collective, uncontrollable risks and toward other localized risks such as loss of personal freedom and business or economic losses (Rahn et al, ).…”
Section: Multilevel Policy Domain Of Food Safety Regulationmentioning
confidence: 99%
“…These obvious symbols are likely to carry more emotional weight than industry or governmental assurances that policy usually works well. Carpenter and Sin (2007) found that the images of fragile children who had been poisoned by Sulfanilamide were influential in triggering a strong outcry that lead to more stringent regulation and licensing for medications in the Food and Drug Act of 1938. Thus, media-generated symbols of health, environmental, or other crises or catastrophes are often used by groups as an important recruiting tool -thereby expanding the issue -and as a form of evidence of the need for policy change.…”
mentioning
confidence: 99%